Philosophical Arguments For The Cosmology of Creation: Al-Kindi's Response to Western Philosophical Views - Shobah, Muhammad Nurush; al-Farizi, Salman (KACA (Karunia Cahaya Allah): Jurnal Dialogis Ilmu Ushuluddin, 2024)
This article is based on al-Kindi's critique of Western philosophy's view of the cosmology of creation. The western theory of creation implies that nature was created from nothing (creatio ex materia). On the other hand, al-Kindi wanted to show the existence of nature from nothing (creatio ex nihilo), one of which was due to materialism. As a result, al-Kindi's various responses to materialism emerged. Al-Kindi recorded three responses, namely Hudust nature, al-Quwwah wa al-fi'l (potential and action), and Ishraqi (illuminative). Based on this problem, this article aims to trace al-Kindi's philosophical thoughts on the cosmology of creation in al-Kindi's interpretation by using critical and descriptive-analytical methods. It sees the emergence of Islamic philosophy as a response to materialism in various philosophical domains that seem to have failed to create a good philosophy, such as the theory of natural creation and causality. To open up the insights of Islamic philosophy, especially those related to nature and causality, al-Kindi offers a philosophical approach by understanding the ontological aspects of the theory of natural creation, the dominance of texts and religion as an epistemology of knowledge. The combination of these two approaches became al-Kindi's offer as a response to the study of Islamic philosophy against Western philosophy.